Microform matters: seasonal variations in peatland protozoic Si pools and the importance of microtopography - Creevy, Angela L.; Puppe, Daniel (Frontiers in Environmental Science, 2025)
Healthy peatlands are the largest terrestrial carbon (C) store despite covering only approximately 3% of total global land surface. However, peatland health is threatened by anthropogenic exploitation and degradation by drainage. Consequently, large-scale ambitious projects to re-wet and restore peatlands have been initiated. It is hoped that they will sequester C and provide a nature-based solution to climate change. The organic-rich peat soils contained in peatlands play an important role in the global C cycle and other biogeochemical cycles, including global silicon (Si) cycling. Testate amoebae (TA) are a dominant group of microbial consumers in peatlands, and their siliceous shells form protozoic Si pools, which represent an important biological sink for Si in these ecosystems. Seasonal variations and the influence of peatland microtopography on protozoic Si pools are unexplored areas of research. In this study, we present data on protozoic Si pools in a former raised bog under restoration management. Our findings show variability in protozoic Si pools between seasons, microtopography, and vegetation cover. There was a clear trend of higher protozoic Si pools in hummocks than in hollows in all seasons, and higher protozoic Si pools were associated with higher water table depth and lower temperatures in colder/wetter months (November/autumn, February/winter) than that in warmer/drier months (May/spring, August/summer). These results suggest that future quantification of protozoic Si pools in peatlands should consider fine-scale spatiotemporal variables as an important feature in the experimental design.